2021
DOI: 10.1002/eji.202149589
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences regulate immune responses in experimental autoimmune encephalomyelitis and multiple sclerosis

Abstract: MS is an autoimmune disease of the CNS that afflicts over 2.5 million people worldwide. There are striking sex differences in the susceptibility to and progression of this disease in humans. Females are twice as likely to develop MS than males, whereas disease progression and disability is more rapid in males compared with females; however, the latter is still controversial. There is growing evidence, mainly from animal models, that innate and adaptive immune responses are different in males and females, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 96 publications
0
17
0
Order By: Relevance
“…Sex-related differences in innate and adaptive immune responses may account for a prevalent female susceptibility to develop EAE symptoms [30]. Myelin oligodendrocyte glycoprotein (MOG ) was used to induce chronic progressive EAE in CB57BL/6 female mice [31], and myelin proteolipid protein (PLP 139-151 ) was used to induce relapsing-remitting EAE in SJL female mice [32].…”
Section: Eae Inductionmentioning
confidence: 99%
“…Sex-related differences in innate and adaptive immune responses may account for a prevalent female susceptibility to develop EAE symptoms [30]. Myelin oligodendrocyte glycoprotein (MOG ) was used to induce chronic progressive EAE in CB57BL/6 female mice [31], and myelin proteolipid protein (PLP 139-151 ) was used to induce relapsing-remitting EAE in SJL female mice [32].…”
Section: Eae Inductionmentioning
confidence: 99%
“…Among the fumaric acid derivates, dimethyl fumarate (DMF) suppresses Th1/Th17 inflammatory responses and promotes a Th2-type response. It is also reported that DMF reduces IL-17 production by CD4 T cells [ 20 ]. Infusion and injectable DMTs are a group of monoclonal antibodies that are comprised of Natalizumab, which prevents lymphocyte adhesion and migration from the peripheral vascular bed to the CNS; Alemtuzumab, which selectively binds the CD52 protein, inducing the clearance of T and B cells and increasing the secretion of brain-derived neurotrophic factor (BDNF) [ 9 , 13 ]; Rituximab, which targets CD20; and Ocrelizumab, which induces an antibody-dependent cytolysis and complement-mediated lysis of B cells [ 9 ].…”
Section: Multiple Sclerosismentioning
confidence: 99%
“…Sex-related differences of innate and adaptive immune responses may account for a prevalent female susceptibility to develop EAE symptoms [25]. Myelin Oligodendrocyte Glycoprotein (MOG…”
Section: Eae Inductionmentioning
confidence: 99%